On performance evaluation of NOMA-aided SIMO multi-hop schemes using energy harvesting and fountain coding based information accumulation - Ngo Hoang An; Lam-Thanh Tu; Tran Trung Duy; Tien-Tung Nguyen (PLoS ONE, 2026)
In this paper, we propose a new non-orthogonal multiple access (NOMA)-aided Single-Input Multiple-Output (SIMO) multi-hop relay scheme using wirelessly energy harvesting (EH) and Fountain Codes (FCs). Specifically, a single antenna source node employs NOMA to transmit two data streams to two multiple antenna destinations with the assistance of N intermediate multiple antenna Decode-and-Forward (DF) relays. The destinations accumulate received information until sufficient data is gathered to successfully recover the original data. This configuration ensures the SIMO structure is maintained across all hops, as the relays utilize multiple antennas for reception and a single antenna for transmission. To enhance channel capacity at the relay and destination nodes, the selection combining (SC) technique is applied. For data transmission, both the source and relay nodes harvest wireless energy from a power station deployed within the network, follows a time-switching approach. We first derive exact expressions for the end-to-end (e2e) instantaneous signal-to-interference-plus-noise ratios (SINRs) at both destinations, along with their corresponding cumulative distribution functions (CDFs) over Rayleigh fading channels. Then, we derive analytical expressions for the average channel capacity (ACC-e2e) and outage probability (OP-e2e) at each destination and validate their accuracy through Monte Carlo simulations.